ChemInform Abstract: Titania Nanostructures: A Biomedical Perspective. Issue 27 (18th June 2015) - Damodaran, Vinod B.; Bhatnagar, Divya; Leszczak, Victoria; Popat, Ketul C.
Abstract Review: 213 refs.